2000
DOI: 10.1046/j.1525-1314.2000.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagenetic and low‐grade metamorphic evolution of chlorite in associated metapelites and metabasites: an integrated TEM and XRD study

Abstract: Chlorite is a common sheet silicate that occurs in various lithologies over a wide grade range involving diagenesis and low‐grade metamorphism. Thus, the reaction progress of chlorite offers a unique opportunity for direct correlation of zonal classification of metasedimentary rocks based on illite crystallinity with metabasite mineral facies. To provide such correlation, chlorite crystallinity indices, apparent mean crystallite sizes and lattice strains, crystallite size distributions and compositions of chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The metabasalt (DG-33) and metadiabase (DG-16) from the Szarvask6 complex have a smaller proportion of corrensitic layers, however, as consistent with a higher grade imposed by regional metamorphic overprinting of the normal MORB alteration sequence. The decrease in percentage of expandable layers with advancing grade was also noted by Arkai and Sadek Ghabrial (1997) and Arkai et al (2000) on the basis of the data obtained using the method of Bettison and Schiffman (1988) that determines the proportions of chlorite in chlorite-smectite mixed-layered material. Other studies have demonstrated that the percentage of expandable layers decreases in these systems with increasing T (or grade) also (Alt, 1999, and references therein).…”
Section: Occurrence Of Smectite-corrensite-chlorite In Lowergrade Metmentioning
confidence: 66%
See 4 more Smart Citations
“…The metabasalt (DG-33) and metadiabase (DG-16) from the Szarvask6 complex have a smaller proportion of corrensitic layers, however, as consistent with a higher grade imposed by regional metamorphic overprinting of the normal MORB alteration sequence. The decrease in percentage of expandable layers with advancing grade was also noted by Arkai and Sadek Ghabrial (1997) and Arkai et al (2000) on the basis of the data obtained using the method of Bettison and Schiffman (1988) that determines the proportions of chlorite in chlorite-smectite mixed-layered material. Other studies have demonstrated that the percentage of expandable layers decreases in these systems with increasing T (or grade) also (Alt, 1999, and references therein).…”
Section: Occurrence Of Smectite-corrensite-chlorite In Lowergrade Metmentioning
confidence: 66%
“…In the first part, we emphasized comparison of ChC indices, as calculated by XRD, and TEM-and XRD-determined thickness values, as well as the relations between ChC and chlorite chemistry. These relations showed that despite differences in composition, mineral assemblages and textures, ChC values of coeval metapelites and metabasites changed in a regular way with increase in grade, and with nearly identical values in coeval pairs (Arkai et al, 2000). In the present paper we describe the evolution of texture, composition and structure of trioctahedral phyllosilicates in detail, emphasizing the mineralogical relations, as a function of reaction progress in pairs of metasedimentary and metabasic rocks over a broad range of grades.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations